A novel method for the synthesis of α-fluoroketones via Claisen rearrangement - Vichai Reutrakul (2018)
Fluorine-facilitated Claisen rearrangement has been employed as a key step in the synthesis of α-fluoroketones 5. The elimination of sulfenic acid from the allyl ethers 3 are effected under FVP conditions. © 1994.